2002
DOI: 10.1208/ps040440
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro examination of the impact of polyethylene glycol 400, pluronic P85, and vitamin E d-a-tocopheryl polyethylene glycol 1000 succinate on P-glycoprotein efflux and enterocyte-based metabolism in excised rat intestine

Abstract: The potential inhibitory effects of 3 excipients (polyethylene glycol [PEG] 400, Pluronic P85, and vitamin E d-a-tocopheryl polyethylene glycol 1000 succinate [TPGS]) on the P-glycoprotein (P-gp) -mediated efflux of digoxin (DIG) and cytochrome P450 3A (CYP3A) -mediated metabolism of verapamil (VRP) have been examined in an in vitro permeability model. Experiments were conducted utilizing rat jejunal tissue mounted in diffusion chambers and included assessment of the serosal to mucosal (s to m) transport of DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(108 citation statements)
references
References 31 publications
6
99
2
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16] It has been reported that several excipients such as Cremophor EL, Tween 80, n-lauryl-b-D-maltopyranoside (LM), Pluronic P85, vitamin E-TPGS, PEGs, sodium caprate and dimethyl-b-cyclodextrin could inhibit the function of Pgp by in vitro and in vivo methods. [6][7][8][9][10][11][12][13][14][15][16] Among these pharmaceutical excipients, Labrasol is one which has been widely used for the solubilization of hydrophobic drugs.17) Labrasol is obtained from coconut oil and has very low toxicity with an LD 50 of 22 g/kg for rats. Recently, it was reported that Labrasol had a strong absorption enhancing effect and that intestinal absorption of various poorly absorbable drugs including gentamicin, insulin and vancomycin was enhanced in its presence.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] It has been reported that several excipients such as Cremophor EL, Tween 80, n-lauryl-b-D-maltopyranoside (LM), Pluronic P85, vitamin E-TPGS, PEGs, sodium caprate and dimethyl-b-cyclodextrin could inhibit the function of Pgp by in vitro and in vivo methods. [6][7][8][9][10][11][12][13][14][15][16] Among these pharmaceutical excipients, Labrasol is one which has been widely used for the solubilization of hydrophobic drugs.17) Labrasol is obtained from coconut oil and has very low toxicity with an LD 50 of 22 g/kg for rats. Recently, it was reported that Labrasol had a strong absorption enhancing effect and that intestinal absorption of various poorly absorbable drugs including gentamicin, insulin and vancomycin was enhanced in its presence.…”
mentioning
confidence: 99%
“…The inlet jejunal cannula was connected to a second peristaltic pump (Amersham Biosciences, Inc.), and perfusate was passed through the lumen at 0.6 ml ⅐ min Ϫ1 from a jacketed reservoir that maintained the perfusate at 37°C (Savina et al, 1981 Ϫ , adjusted to pH 6.5 at 37°C (Schanker et al, 1958). In experiments other than control, perfusate contained either the P-gp inhibitor PSC833 (20 M), the CYP3A inhibitor, midazolam (20 M), or the nonselective P-gp/CYP3A inhibitor ketoconazole (50 M) (Johnson et al, 2002). Body temperature was maintained by a heating mat and lamp, and the exposed jejunal segment was covered by saline-soaked gauze and a clear plastic film.…”
mentioning
confidence: 99%
“…The highest bioavailability with nanocrystals TD-B, compared to the pure RPG and nanocrystals TD-A can be attributed to the inhibitory effect of adsorbed TPGS on the P-gp efflux transporter (41) as well as on CYP3A4 the main enzyme (21,22) involved in the extensive first-pass metabolism of RPG. TPGS has a low critical micelle concentration (0.02%).…”
Section: Oral Bioavailability Studymentioning
confidence: 99%
“…It improves oral absorption of poorly soluble drugs by increasing solubility as well as by modulating P-gp dependent drug efflux mechanism (17)(18)(19)(20). TPGS also exhibits inhibitory effects on cytochrome P450 3A (CYP3A) (21,22).…”
Section: Introductionmentioning
confidence: 99%